Understanding Caregiver Strain in Parkinsonism—A Mixed Methods Approach. (May 2022) - Hand, Annette; Oates, Lloyd L.; Gray, William K.; Dismore, Lorelle L.; Baker, Katherine; Naisby, Jenni; Walker, Richard W.
Background: Parkinsonism, including Parkinson's disease (PD) are progressive neurological conditions. As these condition progress, individuals will need more support with their care needs to maintain independent community-living. Care needs are mainly met by unpaid, informal caregivers, usually close family members or friends. Caregiver strain is thought to lead to the need for care home placement when the caregiver can no longer cope. Objective: To understand predictors of caregiver strain and its influence on care home placement for people with moderate to advanced Parkinsonism. Methods: This is a convergent mixed methods study. Quantitative data, following an adapted stress-appraisal model, were collected on caregiver profile, tasks performed and causes of caregiver strain. Semi-structured, in-depth interviews were conducted with caregivers of people with PD (PwP) who went into a care home during the study period, to develop a deeper understanding of the caregiver role and the factors influencing caregiver strain. Results: Quantitative data were collected from 115 patient caregiver dyads. Interviews were conducted with 10 caregivers. A model to predict caregiver strain was developed and predictors of caregiver strain were identified, such as functional disability and poor caregiver sleep. Conclusion: Our findings further demonstrate the complexity of carer strain. Particular dimensions are identified that need to be addressed within clinical practice to reduce carer strain and support people with Parkinsonism to remain within their own home for as long as possible.